2010
DOI: 10.1111/j.1447-0756.2009.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal mortality and complications associated with cesarean section deliveries in teaching hospitals in Asia

Abstract: Maternal complications were increased by cesarean delivery but elective section may reduce neonatal complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
0
23
1
2
Order By: Relevance
“…On the basis of findings from the survey of 373 facilities across 24 countries in 2008, the World Health Organization (WHO) concluded that unnecessary CS increases the risk of maternal mortality and morbidity, neonatal death, neonatal admission to intensive care [5]. These findings were recently supported by a hospital based prospective study, which used data from nine countries in the wider Asian region (Bangladesh, China, Indonesia, Mongolia, Myanmar, Nepal, Thailand, Sri Lanka, Vietnam) [6]. In addition to potential adverse health consequences, unnecessary CS also causes a substantial economic burden on individual, family and overall society [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of findings from the survey of 373 facilities across 24 countries in 2008, the World Health Organization (WHO) concluded that unnecessary CS increases the risk of maternal mortality and morbidity, neonatal death, neonatal admission to intensive care [5]. These findings were recently supported by a hospital based prospective study, which used data from nine countries in the wider Asian region (Bangladesh, China, Indonesia, Mongolia, Myanmar, Nepal, Thailand, Sri Lanka, Vietnam) [6]. In addition to potential adverse health consequences, unnecessary CS also causes a substantial economic burden on individual, family and overall society [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean deliveries are associated with significantly higher rates of maternal morbidity and mortality than vaginal deliveries. Every obstetrician has experienced a situation where a planned primary cesarean delivery became very complicated, with consequences that might affect the quality of life of the patient [23]. Some women are afraid of a vaginal delivery whereas others, being afraid of a laparotomic procedure, prefer to be delivered vaginally.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk of placenta previa, placenta accreta, uterine scar pregnancy, and uterine rupture is also higher in women who go on to conceive again after having had a previous cesarean section. Because of the presence of the original surgical scar and the possible formation of abdominal adhesion, gynecological surgery after cesarean section is difficult, and the rate of surgical complications is increased . Finally, when the cesarean section rate is lower than 20% to 25%, the perinatal mortality declines as cesarean section increases; however, when the cesarean section rate is higher than this, perinatal mortality improves no further…”
Section: Introductionmentioning
confidence: 99%
“…While Lean Manufacturing offers a highly structured approach to remove inefficiencies, this methodology also aims to achieve maximum customer satisfaction and benefit . LSS originated from Motorola in the 1980s and is increasingly used in the healthcare field …”
Section: Introductionmentioning
confidence: 99%